Pengaruh Model Pembelajaran Gamifikasi terhadap Hasil Belajar Siswa pada Mata Pelajaran Fikih di MTs Muhammadiyah Paraman Ampalu - Ila Angraini; Deswalantri (Lembaga Yasin AlSys, 2026)
Although the influence of learning models on students’ learning outcomes has been widely examined, studies specifically investigating the effectiveness of gamification in Fiqh learning at the madrasah tsanawiyah level remain limited. This study aimed to analyze the effect of the gamification learning model on the Fiqh learning outcomes of students at MTs Muhammadiyah Paraman Ampalu. The study employed a quantitative approach with a Pretest–Posttest Control Group Design involving 25 eighth-grade students selected through random sampling. Data were collected using learning outcome tests in the form of pretests and posttests that met the validity and reliability requirements. The data were analyzed using normality and homogeneity tests and an independent-samples t-test with the assistance of IBM SPSS Statistics. The results showed that the gamification learning model had a significant effect on students’ learning outcomes. This finding was indicated by the higher mean posttest score of the experimental class than that of the control class and a hypothesis-testing significance value of less than 0.05. These results confirm that integrating game elements into learning can improve students’ engagement and learning outcomes. This study enriches the literature on the application of gamification in Islamic Religious Education and confirms that the gamification learning model is appropriate as an alternative model for active, engaging, and student-centered Fiqh learning. Practically, the findings may serve as a consideration for teachers and madrasahs in developing innovative learning strategies to improve students’ learning outcomes.